Recent sea surface temperature trends and future scenarios for the Mediterranean Sea: - Mohamed Shaltout (Oceanologia, 2014)
We analyse recent Mediterranean Sea surface temperatures (SSTs) and their response to global change using 1/4-degree gridded advanced very-high-resolution radiometer (AVHRR) daily SST data, 1982-2012. These data indicate significant annual warming (from 0.24°<s/up>C decade-1 west of the Strait of Gibraltar to 0.51°C decade-1 over the Black Sea) and significant spatial variation in annual average SST (from 15ºC over the Black Sea to 21°C over the Levantine sub-basin). Ensemble mean scenarios indicate that the study area SST may experience significant warming, peaking at 2.6°C century-1 in the Representative Concentration Pathways 85 (RCP85) scenario.